Exophytic focal nodular hyperplasia torsion: A rare cause of sudden-onset epigastric pediatric abdominal pain - Justin Lee; Mark Molitor; Mouied Alashari; William Winters; David E. Skarda (Elsevier, 2014)
Torsion of exophytic liver focal nodular hyperplasia (FNH) is a previously undescribed cause of acute abdominal pain in children. We report two cases of torsion of exophytic focal nodular hyperplasia causing acute abdominal pain successfully treated with surgical resection.